2019
DOI: 10.18039/ajesi.520825
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Fear of Missing Out (FoMO) Levels and Cyberloafing Behaviors of Teacher Candidates

Abstract: The aim of this study is to determine teacher candidates' level of fear of missing out (FoMO) and cyberloafing behaviors which they perform in the computer lab and examine the relationship between them. The study is a quantitative research based on the descriptive survey model. In this context, personal information form, "Fear of Missing Out Scale" which is adapted Turkish by Gökler, Aydın, Ünal & Metintaş (2016) and "Cyberloafing Activities Scale" which is an updated scale by Yaşar (2013) have been used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 10 publications
0
12
0
3
Order By: Relevance
“…The first finding has shown that overall FoMO level of teacher candidates in the study group was slightly below average attainable score in the FoMOS and this can be interpreted as teacher candidates having relatively lower average FoMO. This finding somewhat contradicts with previous research conducted on the matter have shown moderate level of FoMO in preservice teachers studying in a university (Gezgin, Hamutoglu, Gemikonakli & Raman, 2017;Tozkoparan & Kuzu, 2019). Additionally, in other studies investigating overall FoMO levels in university students (who were not explicitly reported to be teacher candidates) moderate levels of overall FoMO have also been reported (Hoşgör et al, 2017;Uyar, Birvural & Karakuyu, 2018).…”
Section: Conclusion and Suggestionsmentioning
confidence: 59%
See 1 more Smart Citation
“…The first finding has shown that overall FoMO level of teacher candidates in the study group was slightly below average attainable score in the FoMOS and this can be interpreted as teacher candidates having relatively lower average FoMO. This finding somewhat contradicts with previous research conducted on the matter have shown moderate level of FoMO in preservice teachers studying in a university (Gezgin, Hamutoglu, Gemikonakli & Raman, 2017;Tozkoparan & Kuzu, 2019). Additionally, in other studies investigating overall FoMO levels in university students (who were not explicitly reported to be teacher candidates) moderate levels of overall FoMO have also been reported (Hoşgör et al, 2017;Uyar, Birvural & Karakuyu, 2018).…”
Section: Conclusion and Suggestionsmentioning
confidence: 59%
“…And yet, it remains a question as to whether teachers and teacher candidates themselves can stay strong against FoMO or if they are equipped with coping mechanisms. The few studies investigating this matter have shown for a Turkish population that both pre-service (Gezgin, Hamutoglu, Gemikonakli, & Raman, 2017;Tozkoparan & Kuzu, 2019) and in-service (Gullu & Serin, 2020) teachers suffer from a moderate level of FoMO on average. However, these studies are not comparative in nature and need to be replicated in order to establish a certain conclusion.…”
Section: Aim and Significance Of The Studymentioning
confidence: 99%
“…It is thought to be a relationship between FoMO and cyberloafing activities. Tozkoparan and Kuzu (2019) found a significant relationship between FoMO and cyberloafing in their study, the sample of which consisted of 141 pre-service teachers. However, it can be seen that studies which investigate teachers' FoMO or cyberloafing behaviour in terms of various variables and observe the relationship between FoMO and cyberloafing behaviour from the point of teachers are limited.…”
Section: Introductionmentioning
confidence: 85%
“…İnsanlar sosyal medyayı; takip ettiği insanların hayatından haberdar olmak, seslerini geniş kitlelere duyurabilmek, aile ve arkadaşlarıyla iletişimlerini sürekli kılabilmek ve kendilerini ifade etmek için kullanırlar. Bireylerin birbirlerinden haberdar olmalarına olanak sağlayan, iletişim kolaylığı sağlayan sosyal medya, bu kolaylıklarının yanında gelişmeleri kaçırma korkusu gibi bazı olumsuzlukları da beraberinde getirmektedir [2]. Amerikalı bilim insanları tarafından 'Fear of Missing Out (FoMO)' olarak tanımlanan bu durum Türkçe'de 'Gelişmeleri Kaçırma Korkusu (GKK)' olarak adlandırılmıştır [3,4].…”
Section: Introductionunclassified